Bayesian logistic regression models for credit scoring - Webster, Gregg (Rhodes University, Faculty of Science, Department of Statistics, 2011)
The Bayesian approach to logistic regression modelling for credit scoring is useful when there are data quantity issues. Data quantity issues might occur when a bank is opening in a new location or there is change in the scoring procedure. Making use of prior information (available from the coefficients estimated on other data sets, or expert knowledge about the coefficients) a Bayesian approach is proposed to improve the credit scoring models. To achieve this, a data set is split into two sets, "old" data and "new" data. Priors are obtained from a model fitted on the "old" data. This model is assumed to be a scoring model used by a financial institution in the current location. The financial institution is then assumed to expand into a new economic location where there is limited data. The priors from the model on the "old" data are then combined in a Bayesian model with the "new" data to obtain a model which represents all the available information. The predictive performance of this Bayesian model is compared to a model which does not make use of any prior information. It is found that the use of relevant prior information improves the predictive performance when the size of the "new" data is small. As the size of the "new" data increases, the importance of including prior information decreases
Keywords: Bayesian statistical decision theory; Credit scoring systems; Regression analysis; Logistic regression analysis; Monte Carlo method; Markov processesFinancial institutions